2017
DOI: 10.1007/s10571-017-0520-2
|View full text |Cite
|
Sign up to set email alerts
|

Acute Impact of Selected Pyridoindole Derivatives on Fos Expression in Different Structures of the Rat Brain

Abstract: The impacts of three pyridoindole derivatives (PDs), designated as PD144, PD143, and PD104, which have previously been shown to have antidepressant (PD144) and anxiolytic (PD143, PD104) properties, were investigated on the Fos expressions in 11 different rat brain areas, including the medial prefrontal cortex, striatum, septum, accumbens nucleus (shell, core), bed nucleus of the stria terminalis, hypothalamic paraventricular nucleus, central amygdala, locus coeruleus, dorsal raphe nucleus, and the solitary tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…It has indeed been reported that various CNS drugs, such typical [12] and atypical antipsychotics [12-14], tricyclic antidepressants [13], and selective 5-HT reuptake inhibitors (SSRIs) [13,15,16], increased c-Fos immunoreactivity in the amygdala, indicating an increased neural excitability in this brain area. In our previous studies, we have found that pyridoindole derivate SMe1EC2M3, a molecule with putative 5-HT reuptake inhibition properties and antidepressant-like behavioral effect [7], stimulated amygdaloid c-Fos immunoreactivity, as well [11]. The fact that SSRIinduced amygdaloid c-Fos immunoreactivity was potentiated by an antagonist of 5-HT1A autoreceptors indicated that 5-HT system is involved in the modulation of amygdaloid neural excitability by antidepressant drugs.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…It has indeed been reported that various CNS drugs, such typical [12] and atypical antipsychotics [12-14], tricyclic antidepressants [13], and selective 5-HT reuptake inhibitors (SSRIs) [13,15,16], increased c-Fos immunoreactivity in the amygdala, indicating an increased neural excitability in this brain area. In our previous studies, we have found that pyridoindole derivate SMe1EC2M3, a molecule with putative 5-HT reuptake inhibition properties and antidepressant-like behavioral effect [7], stimulated amygdaloid c-Fos immunoreactivity, as well [11]. The fact that SSRIinduced amygdaloid c-Fos immunoreactivity was potentiated by an antagonist of 5-HT1A autoreceptors indicated that 5-HT system is involved in the modulation of amygdaloid neural excitability by antidepressant drugs.…”
Section: Discussionmentioning
confidence: 95%
“…twenty-four and one hour before immunoreactivity measurements. C-Fos expression was analyzed, as we have reported previously [11,40]. The rats were anesthetized by a combined treatment of zoletil (30 mg/kg, Virbac, Carros, France) and xylariem (15 mg/kg, Riemser Germany) in the volumes of 0.1 ml and 0.24 ml/300 g b.w., respectively.…”
Section: Assessment Of C-fos Immunoreactivitymentioning
confidence: 99%
See 2 more Smart Citations
“…They include clinical studies on the neuroendocrine response to stressors (Kapsdorfer et al 2017), the role of genetic factors in rheumatoid arthritis (Vernerová et al 2017), and the response to stressors in patients affected by multiple sclerosis . Preclinical studies include alterations in coronary activity (Lazuko et al 2017) in animal models of post-traumatic stress disorder, potentiation of inflammatory responses by repeated stress , the association of stress with immunomodulatory mechanisms (Vargovič et al 2017), and a report of novel antianxiety and antidepressant compounds with central activity (Koprdova et al 2017).…”
mentioning
confidence: 99%